Yield of maize crop irrigated with saline waters - Valdécio dos S. Rodrigues; Francisco M. L. Bezerra; Geocleber G. de Sousa; Jamili N. Fiusa; Kelly N. Leite; Thales V. de A. Viana (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The growing competition for good-quality water is forcing the use of saline water for irrigation in several areas around the world. The objective of this study was to evaluate the influence of different electrical conductivities of irrigation water on the maize production aspects. The study was conducted in the field from August to December 2017 at the Experimental Farm of the Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB), Redenção, CE, Brazil. A randomized complete block design with five irrigation water salinity (1.0, 2.0, 3.0, 4.0 and 5.0 dS m-1) and four repetitions was used. The evaluated variables were: unhusked and husked ear weights, husked ear length and diameter, cob weight, 1000-grain weight and yield. The increase of salt concentration in irrigation water reduced the unhusked and husked ear weights, cob weight, 1000-grain weight and yield. Ear length and diameter were not influenced by the increase in water salinity.